2021
DOI: 10.1038/s41377-021-00499-5
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of an integrated nanophotonic chip-scale alkali vapor magnetometer using inverse design

Abstract: Recently, there has been growing interest in the miniaturization and integration of atomic-based quantum technologies. In addition to the obvious advantages brought by such integration in facilitating mass production, reducing the footprint, and reducing the cost, the flexibility offered by on-chip integration enables the development of new concepts and capabilities. In particular, recent advanced techniques based on computer-assisted optimization algorithms enable the development of newly engineered photonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
(41 reference statements)
0
32
0
Order By: Relevance
“…We have demonstrated proof-of-principle applications of a laser-written vapor-cell (LWVC) for sub-Doppler saturated absorption spectroscopy of rubidium and single beam optical magnetometry based on paramagnetic Faraday rotation. The introduced laser-writing technique provides a suitable interaction volume for precision atomic spectroscopy and atomic quantum sensing with 3D structuring versatility and it has high potential for integration with waveguide-based photonic structures [62,67,68] and optical components [9,10] as well as with optical fibers for chipscale [29] and fiber-coupled [79] atomic sensors. As further development, different geometries and filling techniques based on alkali metal azide [80], mixture of argon and nitrogen [70] as well as other noble gas species like 3 He and 129 Xe [81], will be implemented to optimize specific applications as atomic references, atomic clocks, optical magnetometers and atomic gyroscopes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated proof-of-principle applications of a laser-written vapor-cell (LWVC) for sub-Doppler saturated absorption spectroscopy of rubidium and single beam optical magnetometry based on paramagnetic Faraday rotation. The introduced laser-writing technique provides a suitable interaction volume for precision atomic spectroscopy and atomic quantum sensing with 3D structuring versatility and it has high potential for integration with waveguide-based photonic structures [62,67,68] and optical components [9,10] as well as with optical fibers for chipscale [29] and fiber-coupled [79] atomic sensors. As further development, different geometries and filling techniques based on alkali metal azide [80], mixture of argon and nitrogen [70] as well as other noble gas species like 3 He and 129 Xe [81], will be implemented to optimize specific applications as atomic references, atomic clocks, optical magnetometers and atomic gyroscopes.…”
Section: Discussionmentioning
confidence: 99%
“…typically set by the transverse beam width, is desirable for Doppler-free applications [29], like atomic frequency references [61] and atomic clocks [62,63], as well as for high-sensitivity spin-based atomic sensors like optical magnetometers [64,65] and atomic gyroscopes [66]. The combination of the latter goal with integrated photonics led to state-of-the-art photonic-atomic chips, which make use of hybrid schemes where a separate mm or 𝜇m-sized microfabricated vapor cell is deposited on the top of the photonic chip [67,68]. Then, complex extreme mode-converting apodized grating structure or a nanophotonic spin selector are used to couple light between atomic microcell and photonic waveguides, respectively [67,68], with relatively low efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that the integration of highly conductive doped-Si parts into borosilicate glass walls via an anodicbonding technique [23][24][25][26] enables the fabrication of highand ultra-high-vacuum devices. The Si electrodes afford electric-field control inside the cell directly through the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali atoms are a key resource for numerous emerging chip-scale quantum technologies 1,2 . With the ease of batch fabrication methods, chip-based atomic devices such as vapor cell atomic clocks and magnetometers [3][4][5][6] , quantum gravimeter 7 , and Bose-Einstein condensates on chip [8][9][10][11] have become increasingly attractive for realizing novel quantum device architectures that can be more widely disseminated. As this miniaturization trend continues, there is a growing need to integrate small-scale alkali atom sources directly on chip or within a small volume vacuum cell.…”
mentioning
confidence: 99%